Obesogenic behaviours in South Asian adolescents in England: a literature review and quantitative investigation. (November 2016) - Johal, Gurnam Singh; Bell, Ruth; Hesketh, Therese; Klemera, Ellen; Brooks, Fiona
Abstract: Background: WHO has stated that childhood obesity is one of the most serious challenges facing public health in the 21st century, with obese children and adolescents facing a plethora of health complications and increased risk of many chronic diseases. Using a literature review and quantitative analysis of the WHO Health Behaviour in School-Aged Children (HBSC) data, we aimed to better understand obesogenic behaviours in South Asian adolescents in England. Methods: We searched electronic databases (Embase, Scopus, Medline, Web of Science) from inception of the database to April 10, 2016, and the references of relevant papers. Grey literature including reports and non-peer reviewed sources were also included. Inclusion criteria were: adolescents aged 11–18 years of age, articles in English language, and studies based in England. Quantitative analysis of HBSC data from 2010 examined variables such as physical activity, dietary behaviours, and mental health indicators. We compared adolescents from Bangladeshi, Indian, and Pakistani groups for each variable, by sex, with white British adolescents. Pearson's χ 2 test was carried out to compare all groups against each other. Ethics approval was given by the University of Hertfordshire Ethics committee for Health and Human Sciences (HSK/SF/UH/00007). Ethical sensitivity was also enhanced through the work of reference groups with young people, which informed the conduct of the study within schools. Findings: The HSBC 2010 sample consisted of 51 Bangladeshi, 96 Indian, 111 Pakistani, and 3476 white British adolescents. Two (8·7%) of 23 Bangladeshi girls undertook 5 or more days' physical activity, compared with 744 (44·1%) of 1688 white British girls, 13 (27·7%) of 47 Indian girls, and 16 (33·3%) of 48 Pakistani girls. South Asian adolescents had significantly worse outcomes in terms of number of times physical activity was undertaken per week (p=0·023) or any physical activity in the previous 7 days (p=0·002). 11 (20·0%) of 55 Pakistani girls never ate vegetables or ate them less than once a week, compared with 94 (5·3%) of 1771 white British girls (consumption of vegetables, p<0·0005). Interpretation: Key findings from the literature review and HBSC 2010 data were that South Asian adolescents have lower physical activity levels compared with their white peers, have worse dietary behaviours, and have barriers to engaging in healthier lifestyles, compared with their white British counterparts. These negative lifestyle behaviours will need careful consideration of upstream policy and local health service provision and interventions in South Asian adolescents in England. Taking this evidence into action will be crucial to address the obesity epidemic and reduce existing health inequalities. Funding: None.